Seropositivity of Hepatitis C Infection Among Voluntary and Replacement Blood Donors in District Hospital, Hanumangarh. (International Journal of Food and Nutritional Sciences, 2022)
Introduction: HCV is a causative agent of Post transfusion Hepatitis. Hepatitis C is a silent disease as remain asymptomatic in acute phase. Currently, Hepatitis C is the most common cause of liver transplant and a major problem around the world. Besides various route of transmission, the most common source for Viral Hepatitis C (VHC) transmission is the blood transfusion. Among Blood donors, this infection is more prevalent in replacement donors than in voluntary donors.Aims and Objectives: A cross sectional Hospital based study was conducted on 3209 healthy blood donors which include 2581(80.4%) voluntary donors and 628(19.6%) replacement donors to evaluate the HCV seropositivity in Dist- Hanumangarh and to assess the socio-demographic characters for Hepatitis C Infection. All the blood samples were tested for anti-HCV antibody by latest generation Enzyme Linked Immunosorbant Assay. The result of the study was analyzed statistically using χ2 test.Result: HCV seropositivity among 3209 blood donors were evaluated as 0.7%, this was significantly lower in voluntary than in replacement donors (0.7% v/s 1%). Maximum seropositivity was observed in male and age group of 20-29 years (1.11%, 17/1521).HCV was more prevalent among rural population in voluntary donors and in urban population in replacement donors. Seropositivity for male (voluntary v/s replacement) was not observed statistically significant.Conclusion: The study concluded voluntary blood donation as a safe side so efforts are required to increase voluntary blood camp.